Non-Human Primate iPSC Generation, Cultivation, and Cardiac Differentiation under Chemically Defined Conditions - Michael Stauske; Ignacio Rodriguez Polo; Wadim Haas; Debbra Yasemin Knorr; Thomas Borchert; Katrin Streckfuss-Bömeke; Ralf Dressel; Iris Bartels; Malte Tiburcy; Wolfram-Hubertus Zimmermann; Rüdiger Behr (Cells, 2020)
Non-human primates (NHP) are important surrogate models for late preclinical development of advanced therapy medicinal products (ATMPs), including induced pluripotent stem cell (iPSC)-based therapies, which are also under development for heart failure repair. For effective heart repair by remuscularization, large numbers of cardiomyocytes are required, which can be obtained by efficient differentiation of iPSCs. However, NHP-iPSC generation and long-term culture in an undifferentiated state under feeder cell-free conditions turned out to be problematic. Here we describe the reproducible development of rhesus macaque (Macaca mulatta) iPSC lines. Postnatal rhesus skin fibroblasts were reprogrammed under chemically defined conditions using non-integrating vectors. The robustness of the protocol was confirmed using another NHP species, the olive baboon (Papio anubis). Feeder-free maintenance of NHP-iPSCs was essentially dependent on concurrent Wnt-activation by GSK-inhibition (Gi) and Wnt-inhibition (Wi). Generated NHP-iPSCs were successfully differentiated into cardiomyocytes using a combined growth factor/GiWi protocol. The capacity of the iPSC-derived cardiomyocytes to self-organize into contractile engineered heart muscle (EHM) was demonstrated. Collectively, this study establishes a reproducible protocol for the robust generation and culture of NHP-iPSCs, which are useful for preclinical testing of strategies for cell replacement therapies in NHP.